The Role of the Embassy of the Republic of Indonesia Kuala Lumpur in Addressing the Rights of Indonesian Women Migrant Workers - Sundari, Rio; Andini, Diva Febby (Hasanuddin Journal of International Affairs, 2025)
The purpose of this research is to analyze how the role of the Embassy of the Republic of Indonesia Kuala Lumpur in tackling the problem of the rights of Indonesian women migrant workers. With the increasing population in Indonesia, job opportunities within the country are limited, which has led to swelling unemployment rates in Indonesia, and Indonesians migrating to neighboring countries, such as Malaysia. Workers, especially women, are often trapped in unfair and high-risk work situations, such as being denied their rights to unpaid wages for long periods. Violations of women migrant workers' rights include lack of legal protection, massive labor exploitation, and gender discrimination that often occurs in the workplace. The Embassy of the Republic of Indonesia Kuala Lumpur's involvement in facilitating these rights is crucial. The researcher used a descriptive qualitative research approach, the initial research information came from interviews with relevant parties, such as reports, articles, books, or pre-existing databases. The Indonesian Embassy in Kuala Lumpur is also responsible for providing protection, assistance, and advocacy for Indonesian women migrant workers who experience problems in Malaysia. The Indonesian government and the Indonesian Embassy in Kuala Lumpur need to raise public awareness about the importance of protecting the rights of women migrant workers and the dangers faced by them. By using more effective policies to protect the rights of women migrant workers, such as policies on the protection of migrant workers' rights.